Subclinical Myocardial Injury and Global Cognitive Performance - Shubham Tomar, MBBS, MPH; Karita C.F. Lidani, MD, MSc, PhD; Aline A.I. Moraes, MD, PhD; Shi Huang, PhD; Christian Oakley, BS; Khurram Nasir, MD, MPH; Michael J. Blaha, MD, MPH; Susan R. Heckbert, MD, PhD; Timothy M. Hughes, PhD; Christopher R. deFilippi, MD; Yader Sandoval, MD; Allan S. Jaffe, MD; et al. (JACC: Advances, 2025)
Background: Cognitive impairment is common in cardiovascular disease (CVD) patients. Objectives: The purpose of this study was to evaluate the relationship of myocardial injury, measured by high-sensitivity cardiac troponin T (hs-cTnT), with global cognitive performance and its decline over time. Methods: Hs-cTnT assessed at baseline (2000-2002) and exam 5 (2010-2012) in 4,445 participants. Cognitive function evaluated using the Cognitive Abilities Screening Instrument (CASI) at exams 5 and 6 (2016-2018). Subclinical myocardial injury defined as hs-cTnT above limits of detection but below 19 ng/L, while clinical myocardial injury >19 ng/L. Cognitive decline was a >5 point decrease in CASI scores from exam 5 to 6. Regression analysis assessed the association of hs-cTnT levels with CASI scores and their decline. Results: Mean age at baseline was 60 years with 53% females. At baseline and exam 5, 63% and 87% had subclinical myocardial injury, respectively. Higher Log10(hs-cTnT) at baseline (β = −1.45 [95% CI: −2.5 to −0.41]), exam 5 (β = −1.63 [95% CI: −2.7 to −0.59]), and greater baseline to exam 5 increase (β = −1.42 [95% CI: −2.8 to −0.06]) were associated with lower CASI scores at exam 5, after adjusting for demographics, education, language, and apolipoprotein E status. These estimate lost significance after CVD risk factor adjustment. Higher Log10(hs-cTnT) at baseline (OR: 2.02 [95% CI: 1.29-3.12]), exam 5 (OR: 2.52 [95% CI: 1.56-4.05]), or greater baseline to exam 5 increase (OR: 2.22 [95% CI: 1.18-4.15]) were associated with higher odds of cognitive decline in fully adjusted models. Conclusions: In community-based cohort, higher or increasing hs-cTnT was associated with greater odds of future cognitive decline over 6 years of follow-up.